Genetics in Colorectal Cancer: A Narrative Literature Review - Billy Peter Manawan (Natural Sciences Engineering and Technology Journal, 2021)
Colorectal cancer (CRC) is the third most commonly diagnosed form of cancer globally, which is about 11% of all cancer diagnoses. Obesity, together with kind of sedentary lifestyle, red meat consumption, tobacco, and alcohol consumption are considered as predisposing factors of progression of CRC. This literature review was aimed to describe genetic aspect in colorectal cancer. In the development of colorectal cancer, genetic factors having a role in its incidence. The hereditary type of colorectal cancer was divided into two types is polyposis and Lynch syndrome which have each and different mechanism and genetic pattern. Lynch syndrome contributes to 3–5% of CRC cases and is caused by a germline mutation in one of four genes associated with the DNA mismatch repair (MMR) system; MLH1, MSH2, MSH6, or PMS2. In polyposis, there are some types such as familial adenomatous polyposis (FAP) which is mostly caused by APC mutation, MYH-associated polyposis, and the rare hamartomatous polyposis syndromes. In conclusion, genetic testing and better family history documentation can enable those with a hereditary predisposition for the neoplasm to take preventive measures.